PENGARUH PERSONAL COST, KOMITMEN ORGANISASI, TEKANAN KETAATAN, DAN DUKUNGAN ORGANISASI TERHADAP WHISTLEBLOWING - Amelia, Riska; Indriani, Poppy (ITB AAS Indonesia Surakarta, 2024)
Even now today, organizations almost never use whistleblowing, despite the many dangers that whistleblowers may face. As a result, it can be very difficult to find out about any fraudulent activity taking place within the company. The aim of this research is to identify the variables that influence the decision of KONI Sumsel employees to report violations. The research population consisted of 40 South Sumatra KONI personnel, and 32 people were selected using a non-probability selection method known as saturated sampling to be used as samples. Quantitative research is the research methodology used. A Likert scale was used for data collection, and SPSS version 26 software was used for the multiple linear regression data processing approach. The research findings show that although personal costs, organizational commitment, and compliance pressure do not influence employees' intention to report errors, the organizational support variable has a positive and significant influence.